P-Type ATPases Methods and Protocols - Bublitz, Maike; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2016)
This volume provides a broad collection of protocols for many of the common experimental techniques used for the characterization of P-type ATPases. P-Type ATPases: Methods and Protocols provides comprehensive practical instructions for all researchers in the P-type ATPase field, from the protein biochemist to the mouse geneticist, covering the identification and classification, isolation, purification, in vitro characterization, knock-out studies, as well as crystallization and structural analysis. Written for the Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, P-Type ATPases: Methods and Protocols aims to ensure successful results in the further study of this vital field of research.
An Introduction to P-type ATPase research -- Purification of Na,K-ATPase from Pig Kidney -- Preparation of Ca2+-ATPase1a Enzyme from Rabbit Sarcoplasmic Reticulum -- Isolation of H+/K+-ATPase-enriched Membrane Fraction from Pig Stomachs -- Overproduction of PiB-type ATPases -- Coordinated Overexpression in Yeast of a P4-ATPase and its Associated Cdc50 Subunit: The Case of the Drs2p/Cdc50p Lipid Flippase Complex -- The Plasma Membrane Ca2+-ATPase: Purification by Calmodulin Affinity Chromatography, and Reconstitution of the Purified Protein -- Expression of Na,K-ATPase and H,K-ATPase Isoforms With The Baculovirus Expression System -- Time-dependent Protein Thermostability Assay -- Colorimetric Assays of Na,K-ATPase -- ATPase Activity Measurements by an Enzyme-Coupled Spectrophotometric Assay -- Antimony-Phosphomolybdate ATPase Assay -- ATPase Activity Measurements using radiolabeled ATP -- Assaying P-type ATPases Reconstituted in Liposomes -- Coupling ratio for Ca2+ Transport by Calcium Oxalate Precipitation -- Calcium Uptake in Crude Tissue Preparation -- Measuring H+ Pumping and Membrane Potential Formation in Sealed Membrane Vesicle Systems -- Assay of Flippase Activity in Proteoliposomes using Fluorescent Lipid Derivatives -- The use of Metal Fluoride Compounds as Phosphate Analogs for Understanding the Structural Mechanism in P-type ATPases -- Phosphorylation/Dephosphorylation Assays -- Tryptophan Fluorescence Changes Related to Ca2+-ATPase Function -- Determination of the ATP Affinity of the Sarcoplasmic Reticulum Ca2+-ATPase by Competitive Inhibition of [g-32P]TNP-8N3-ATP Photolabeling. 23. Ca2+ Binding and Transport Studied with Ca2+/EGTA Buffers and 45Ca2+ 24. Assay of Copper Transfer and Binding to P1B-ATPases 25. Voltage Clamp Fluorometry of P-Type ATPases 26. Electrophysiological Measurements on Solid Supported Membranes 27. Electrophysiological Characterization of Na,K-ATPases Expressed in Xenopus laevis Oocytes Using Two-Electrode Voltage Clamping 28. Functional Studies of Na+,K+-ATPase using Transfected Cell Cultures 29. HPLC Neurotransmitter Analysis 30. Behavior Test Relevant to a2/a3Na+/K+-ATPase Gene Modified Mouse Models 31. Zebrafish Whole-mount in situ Hybridization Followed by Sectioning 32. Whole-mount Immunohistochemistry for Anti-F59 in Zebrafish Embryos (1-5 days Post Fertilization (dpf)) Canan Doganli 33. Cell-based Lipid Flippase Assay Employing Fluorescent Lipid Derivatives 34. Transient Expression of P-type ATPases in Tobacco Epidermal Cells 35. Lipid Exchange by Ultracentrifugation 36. Reconstitution of Na+, K+-ATPase in Nanodiscs 37. Crystallization of P-type ATPases by the High Lipid-detergent (HiLiDe) Method 38. Two-dimensional Crystallization of the Ca2+-ATPase for Electron Crystallography 39. Two-dimensional Crystallization of Gastric H+,K+-ATPase for Structural Analysis By Electron Crystallography 40. MD Simulations of P-type ATPases in a Lipid Bilayer System 41. Computational Classification of P-Type ATPases 42. Molecular Modeling of Fluorescent SERCA Biosensors 43. How to Compare, Analyze and Morph Between Crystal Structures of Different Conformations: The P-type ATPase Example Jesper L .
Keywords: Life sciences; Cell membranes; Life Sciences; Membrane Biology; Electronic books